Effect of biochar derived from faecal matter on yield and nutrient content of lettuce (Lactuca sativa) in two contrasting soils - Woldetsadik, D.; Drechsel, Pay; Marschner, B.; Itanna, F.; Gebrekidan, H. (Springer, 2018)
Background: Faecal matter biochar offers an interesting value proposition where the pyrolysis process guaranties a 100% pathogen elimination, as well as significant reduction in transport and storage weight and volume. Therefore, to evaluate the effect of (1) biochar produced from dried faecal matter from household based septic tanks, and (2) N fertilizer, as well as their interaction on yield and nutrient status of lettuce (Lactuca sativa), lettuce was grown over two growing cycles under glasshouse on two contrasting soils amended once at the start with factorial combination of faecal matter biochar at four rates (0, 10, 20 and 30 t ha-1) with 0, 25 and 50 kg N ha-1 in randomized complete block design. Results: For both soils, maximum fresh yields were recorded with biochar and combined application of biochar with N treatments. However, the greatest biochar addition effects (with or without N) with regard to relative yield were seen in less fertile sandy loam soil. We have also observed that faecal matter biochar application resulted in noticeable positive residual effects on lettuce yield and tissue nutrient concentrations in the 2nd growing cycle. For both soils, most nutrients analyzed (N, P, K, Mg, Cu and Zn) were within or marginally above optimum ranges for lettuce under biochar amendment. Conclusions: The application of faecal matter biochar enhances yield and tissue nutrient concentrations of lettuce in two contrasting soils, suggesting that faecal matter biochar could be used as an effective fertilizer for lettuce production at least for two growing cycles. Moreover, the conversion of the faecal matter feedstock into charred product may offer additional waste management benefit as it offers an additional (microbiologically safe) product compared to the more common co-composting.